Analysis of spatial literacy in grade V volume material reviewed from learning style - Ina Wijayanti; Nurafni Nurafni (Universitas Pendidikan Indonesia, 2025)
The background of this study is the importance of spatial literacy skills in understanding the concept of three-dimensional geometry, as well as differences in students' learning style preferences in processing information. This study aims to determine the spatial literacy skills of grade V elementary school students on volume material in terms of visual, auditory, and kinesthetic learning styles. This research uses a descriptive qualitative approach with the subject of three students who each represent visual, auditory, and kinesthetic learning styles, and have high academic abilities. The instruments used were the learning style questionnaire, the spatial literacy test, and the interview guidelines. The time triangulation technique was used to ensure the validity of the data, and the analysis was conducted using the Miles and Huberman model. The results showed that students with visual learning styles excelled in the visualization and communication domains, auditory students stood out in spatial reasoning. In contrast, kinesthetic students showed low achievement in all three domains. The findings indicate that learning styles influence spatial literacy achievement and the importance of learning approaches that are adaptive to students' learning characteristics. Abstrak Latar belakang penelitian ini adalah pentingnya kemampuan literasi spasial dalam memahami konsep geometri tiga dimensi, serta adanya perbedaan preferensi gaya belajar peserta didik dalam memproses informasi. Penelitian ini bertujuan untuk mengetahui kemampuan literasi spasial peserta didik kelas V sekolah dasar pada materi volume ditinjau dari gaya belajar visual, auditori, dan kinestetik. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan subjek tiga peserta didik yang masing-masing mewakili gaya belajar visual, auditori, dan kinestetik, serta memiliki kemampuan akademik tinggi. Instrumen yang digunakan berupa angket gaya belajar, tes literasi spasial, dan pedoman wawancara. Teknik triangulasi waktu digunakan untuk menjamin keabsahan data, dan analisis dilakukan dengan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa peserta didik dengan gaya belajar visual unggul dalam domain visualisasi dan komunikasi, peserta didik auditori menonjol dalam penalaran spasial, sedangkan peserta didik kinestetik menunjukkan capaian yang rendah pada ketiga domain. Temuan ini mengindikasikan bahwa gaya belajar berpengaruh terhadap capaian literasi spasial dan pentingnya pendekatan pembelajaran yang adaptif terhadap karakteristik belajar peserta didik. Kata Kunci: gaya belajar; literasi spasial; volume